Menjadi SDM Unggul di Era Digital Pada BKPRMI Kabupaten Asahan - Santoso Santoso; Elly Rahayu; Wan Mariatul Kifti; Syahira Syahira; Tri Anjar Ningsih (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2022)
Abstract: Community service activities were carried out by the STMIK Royal lecturer team in the form of HR development training with the theme "Becoming Excellent Human Resources in the Digital Era" for the Regional Management Board and the District BKPRMI District Management Board whose implementation was centered in the hall of the Kisaran Timur sub-district sub-district office on 15-16 January 2022 . There are several goals to be achieved in this activity, namely: providing knowledge about HR in the Digital era, providing knowledge about HR development strategies, and providing knowledge about the benefits of technology in the da'wah process. This activity was attended by 20 representatives from the sub-district. The results of this activity are the implementation of HR development training and the implementation of collaboration between STMIK Royal Kisaran and the BKPRMI organization of Asahan Regency as well as mapping the problems and potential of human resources in the management of BKPRMI, especially in the field of Technology to carry out further training activities. Keywords: BKPRMI; HR; Superior; Digital  Abstrak: Kegiatan pengabdian kepada masyarakat  yang dilaksanakan tim dosen STMIK Royal  dalam bentuk Pelatihan pengembangan SDM dengan tema  “Menjadi SDM Unggul Di Era Digital” bagi   Dewan Pengurus Daerah dan Dewan Pengurus Kecamatan BKPRMI Kabupaten   yang pelaksanaanya dipusatkan di aula kantor camat Kecamatan Kisaran Timur pada tanggal 15-16 Januari 2022  Ada beberapa tujuan yang ingin dicapai pada kegiatan ini yaitu: memberikan pengetahuan tentang SDM di era Digital, memberikan pengetahuan tentang strategi pengembangan SDM, dan  memberikan pengetahuan tentang manfaat teknologi dalam proses dakwah. Kegiatan ini dihadiri 20  perwakilan dari kecamatan. Hasil dari kegiatan ini adalah terlaksananya pelatihan pengembangan SDM dan dilaksanakannya kerjasama antara STMIK Royal Kisaran dengan organisasi BKPRMI Kabupaten Asahan serta terpetakannya permasalahan serta potensi SDM pada kepengurusan BKPRMI terutama bidang Teknologi guna melakukan kegiatan pelatihan selanjutnya. Kata Kunci: BKPRMI; SDM; Unggul; Digital